Neoliberal trends in collective bargaining and employment regulation in Spain, Italy and the UK: From institutional forms to institutional outcomes. (December 2019) - López-Andreu, Martí
This article discusses the effect of neoliberal trends in employment regulation during the 2008 recession. Liberalization in employment institutions is a long-term trend reinforced by the implementation of austerity policies. I use EU-SILC panel data to discuss these trends in Spain, Italy and the UK in three periods: before the crisis (2004–2007), during the crisis (2007–2010) and under austerity (2010–2013). Although liberalization reforms interacted with the existing institutional architectures, I find a common trend towards greater employer discretion. Crucially, this trend in institutional outcomes appears in countries with different formal institutional characteristics in employment and collective bargaining.